Nurses' work process in an emergency hospital service - Simone Kroll Rabelo; Suzinara Beatriz Soares de Lima; José Luís Guedes dos Santos; Valdecir Zavarese da Costa; Emilene Reisdorfer; Tanise Martins dos Santos; Jocelaine Cardoso Gracioli (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: to analyze the nurses' work process in an Emergency Hospital Service. Methods: a qualitative, exploratory and descriptive research conducted with 17 nurses from the emergency service of a high complexity hospital in southern Brazil. Data were collected through interviews, focus group and document analysis. Data analysis followed the thematic content analysis framework. Results: four categories emerged: Work environment characteristics; Assistance dimension; Management dimension; Care management. Final Considerations: the nurses' work process in Emergency Hospital Service is characterized by the peculiarities of the setting, with centrality in care and care management aiming at quality care and safety to patients.